Perceptions of risk on vacation among visitors to Istanbul. Issue 1 (14th January 2019) - Ozascilar, Mine; Mawby, Rob I.; Ziyalar, N.
Abstract : Purpose: The purpose of this paper is to focus on the perceptions of risk from specific crimes held by tourists at the start of their vacation in the Turkish city of Istanbul. Design/methodology/approach: The paper describes findings from Phase 1 of a two-phase research programme, during which 210 arrivals at the Ataturk airport were asked about their perceptions of their safety from crime while in the city and their intentions vis-à-vis the adoption (or otherwise) of basic safety precautions, using a 32-question self-completion questionnaire. Findings: The findings confirm those of earlier studies that tourists, unlike citizens in general, tend to have low expectations of their vulnerability to crime. However, variables associated with fear in conventional surveys were not generally related to the perceptions of risk. The clearest association was between prior knowledge of crime in Istanbul and perceptions of risk. The lack of any strong relationship between perceptions of risk and intent to adopt safety precautions is then discussed. Research limitations/implications: The study is limited to visitors to one city and to English-speaking tourists. Practical implications: The implication here is that if tourist centres wish to reduce crime it is not sufficient to focus on "educating" tourists on the dangers, but that more emphasis should be placed on crime prevention methods that put the onus on the host environment. Social implications: From a criminological perspective, two points appear particularly important. First, the relationship between fear (in all its manifestations) and risk is not constant. It may differ in different physical and social contexts. Second, if, following routine activity theory, policy makers wish to focus on changing people's behaviour in order to maximise their safety, in different contexts different publics may vary in their willingness or resistance to change. Originality/value: This study is original as it focusses on tourists to a specific destination at the beginning of their holiday.